The effect of adding Syrian natural zeolite to broiler litter on the humidity of the litter and in the indoor air of the barn during the winter season - نيصافي, علي; قره علي, أحمد; العيسى, بشرى; جلنكريان, بيرنا كريكور (Latakia University Journal -Biological Sciences Series, 2021)
A research experiment was conducted from 2019 to 2021 season. The research studied during five weeks for each fattening period, the indicators of the humidity of the litter consisting of sawdust and the temperatures and the relative humidity of the indoor air of the broiler farm during the winter season (December - January) when 3000 broilers belonging to the Roos hybrid. The research results indicated that: - The average humidity of the broiler litter in the control treatment that did not add zeolite to the litter in the first week was 45.86%, while for the fifth week it reached 73.01%, as the amount of increase when compared between the two periods was 27.15%. - After adding the zeolite to the litter in three different ratios for the three treatments of the experiment, the average values were as follows: The control Tz0 (0%) 61.01%, Tz1 (25%) 53.83%, Tz2 (50%) 43.78%, Tz3 (75%) 38.38%. The results showed that there were significant differences between the averages during the care period. In addition, the litter moisture percentage decreased significantly in the three treatments compared with the control treatment. - The average temperature and relative humidity of the indoor air of the farm were monitored; the average temperature was as follows: 20.96 °C, 20.62 °C, 20.44 °C, 20.32 °C consequently. We notice a little changes in the average of the temperature between the four treatments. While the average relative humidity of the air decreased significantly in the three treatments compared to the control treatment, where the following values were recorded: 79.84 %, 70.66 %, 67.14%, 65.64 % consequently.